Determining the onset of grinding burn using Magnetic Barkhausen Noise - Opoku, Kevin S (Cranfield University, 2005)
A study of the quick non-destructive technique of Magnetic Barkhausen Noise (MBN) in detecting the onset of grinding burn in the absence of any microstructural changes during grinding has been undertaken. 51CrV4 Steel is a used in industry for manufacturing automotive parts (Nissan). Uniaxial tensile tests using a coarse surface whilst taking in situ MBN measurements were used to calibrate MBN to residual stress for hard and soft samples of 51CrV4. X-ray diffraction tests of some ground samples of hard and soft 51CrV4 samples were used to correlate the obtained calibration curves. A depth profile analysis was also carried out from results of MBN and XRD measurements of 51CrV4 soft and hard samples ground at different specific material removal rates. The MBN Vrms and Vpeak parameters in the elastic deformation region were shown to behave linearly with total stress. A predictive model to calculate residual stress values showed good correlation in terms of the direction but the magnitude of the error was poor within its working limits. The Vrms and Vpeak and FWHM also showed a sharp change in the trend during the change from compressive to tensile stress. The application of the MBN technique in detecting grinding burn before it happened meant that waste could be limited and grinding processes optimised without compromising the surface integrity of components.